The Development of Vaccines from Synthetic Tumor‐Associated Mucin Glycopeptides and their Glycosylation‐Dependent Immune Response. Issue 11 (23rd November 2021) - Stergiou, Natascha; Urschbach, Moritz; Gabba, Adele; Schmitt, Edgar; Kunz, Horst; Besenius, Pol
Abstract: Tumor‐associated carbohydrate antigens are overexpressed as altered‐self in most common epithelial cancers. Their glycosylation patterns differ from those of healthy cells, functioning as an ID for cancer cells. Scientists have been developing anti‐cancer vaccines based on mucin glycopeptides, yet the interplay of delivery system, adjuvant and tumor associated MUC epitopes in the induced immune response is not well understood. The current state of the art suggests that the identity, abundancy and location of the glycans on the MUC backbone are all key parameters in the cellular and humoral response. This review shares lessons learned by us in over two decades of research in glycopeptide vaccines. By bridging synthetic chemistry and immunology, we discuss efforts in designing synthetic MUC1/4/16 vaccines and focus on the role of glycosylation patterns. We provide a brief introduction into the mechanisms of the immune system and aim to promote the development of cancer subunit vaccines. Abstract : Tumor‐associated carbohydrate antigens, TACAs, are overexpressed as altered‐self in most common epithelial cancers. This review discusses the development of glycopeptide anti‐tumor vaccines, highlight both the synthetic chemistry as well as immunological evaluation. Recent efforts in designing synthetic tumor‐associated mucin 1, 4 and 16 antigens and vaccines are discussed, with a particular focus on the role of glycosylation patterns.